Size, Length-Weight Relationship And Condition Factor Of Banggai Cardinal Fish, Pterapogon Kauderni Koumans, 1933 In Lembeh Strait North Sulawesi - Rully Lempoy; Ari B. Rondonuwu; Nego E. Bataragoa (Sam Ratulangi University, 2020)
This study aims to determine the size distribution and the relationship between length and weight and condition factors of Banggai Cardinalfish (Pterapogon kauderni) in the Lembeh Strait. Fish samples were obtained by using Chang Net in the Lembeh Strait. Total fish caught were 150 individuals from three sites namely Serena Besar Island, the waters in front of LIPI and the waters in front of Papusungan village with 50 fish each. The size distribution of Pterapogon kauderni fish ranges from 4.13 - 8.92 cm and dominated by the size class of 7.13 - 7.72 cm while the size class of 4.13 - 4.72 cm only contains 3 individuals. The length-weight relationship of male fish is W = 0.0285 L2.6496 (n = 77; R2 = 0.7231), and female fish W = 0.837 L2.0723 (n = 73; R2 = 0.6626). The growth pattern analysis shows a negative allometric pattern both for males and females while the condition factors of male fish are 1.020 ± 0.202 and female 1.027 ± 0.236.Keywords: Kauderni pterapogon, distribution size, length-weight relationship, condition factorAbstrakPenelitian ini bertujuan untuk mengetahui distribusi ukuran dan hubungan panjang berat serta faktor kondisi ikan Capungan Banggai (Pterapogon kauderni) yang ada di Selat Lembeh. Sampel ikan diperoleh dengan cara ditangkap menggunakan Chang Net di Selat Lembeh. Total hasil tangkapan adalah 150 individu masing-masing 50 di Pulau Serena Besar, Perairan depan LIPI dan Perairan depan desa Papusungan. Sebaran ukuran ikan Pterapogon kauderni berkisar antara 4,13 – 8,92 cm dan didominasi oleh kelas ukuran 7,13 – 7,72 cm sedangkan kelas ukuran 4,13 – 4,72 cm hanya terdapat 3 individu. Hubungan panjang-berat ikan jantan adalah W = 0,0285L2,6496 & (n = 77 ; R2 = 0,7231), ikan betina W = 0,837L2,0723 (n = 73 ; R2 = 0,6626). Analisis pola pertumbuhan menunjukan pola pertumbuhan allometrik negatif baik jantan maupun betina. sedangkan Faktor kondisi ikan jantan 1,020 ± 0,202 dan betina 1,027 ± 0,236.Kata kunci: Pterapogon kauderni, sebaran ukuran, panjang berat, faktor kondisi